The Effectiveness of Social Media Campaign Poster to Prevent Cyberbullying Among Teenagers in Malaysia Through Illustration - Syed Hussein, Syed Nor Azlee Sha; Mohd Shuib, Ahmad Sofiyuddin (Idealogy Journal; Vol 3 No 2 (2018): Idealogy Journal (September 2018)DO - 10.24191/idealogy.v3i2.75, 2018)
This paper aims to discuss the effectiveness of social media campaign poster to prevent cyberbullying among teenagers in Malaysia through illustration. The user of smartphone are increasing every year and cyberbullying in Malaysia also increasing every year, mostly among teenagers. Every teenagers could say that they need smartphone but without supervision from parents, it could bring the harness to their children. Not only teenager need to prevent from cyberbullying, parents needs to play their part to stop this cyberbullying. The researcher make a survey using qualitative method to identify how to let people, especially teenager read the message in media social campaign poster through illustration. Besides that, the field survey are very suitable for do the survey about cyberbullying among teenagers in the school because this objective are focusing teenager than adult. The finding of this research will help to create the message or awareness about how badly is cyberbullying among teenagers in social media poster through illustration. The study will help to reduce the percentage of cyberbullying among teenagers in Malaysia and it will help the society become healthy even in real life or in internet. Keywords: poster; illustration; cyberbullying; social media